Factors Affecting the Aluminum, Arsenic, Cadmium and Lead Concentrations in the Knee Joint Structures - Li, Guoyong; Xiong, Chunfeng; Xu, Wenhua; Mei, Runhong; Cheng, Tao; Yu, Xuefeng (Frontiers in Public Health, 2021)
Background: Toxic elements, such as aluminum (Al), arsenic (As), cadmium (Cd), and lead (Pb), are persistent environmental pollutants that can cause adverse effects on the health of exposed individuals. Bone is one of the primary target organs of accumulation and potential damage from toxic elements. Objectives: This study was performed to determine the Al, As, Cd, and Pb concentrations in the femoral cancellous bone, femoral cartilage, anterior cruciate ligament, meniscus, tibial cartilage, tibial cancellous bone and infrapatellar fat pad. Furthermore, the aim of this study was to explore the relationships between toxic element concentrations and related factors such as gender, age, place of residence, hypertension and diabetes, and to determine the correlations among these toxic elements in knee joint structures. Methods: The samples used this study were collected from 51 patients following total knee arthroplasty. The Al, As, Cd, and Pb concentrations were determined using inductively coupled plasma optic emission spectrometry. Results: Significant differences were found in the Al, As, Cd, and Pb concentrations among the knee joint structures. Cd concentration in the tibial cancellous bone in women was significantly higher than in men. Pb concentration in the infrapatellar fat pad of urban patients was significantly higher as compared to rural patients. Al concentrations in the femoral cancellous bone, femoral cartilage, anterior cruciate ligament, meniscus and tibial cartilage were significantly higher in patients living in urban areas than in rural areas. As concentration in the tibial cancellous bone of diabetic patients was significantly higher compared to non-diabetic patients. In addition, significant Spearman's positive correlations were found between Al and Pb in the knee joint structures. Conclusion: The obtained results of the investigated toxic elements may serve as a basis for establishing the reference values of Al, As, Cd, and Pb in the knee joint structures. The results reported in the study provides novel data regarding the relationships between the toxic element concentrations and gender, age, place of residence, hypertension and diabetes in the studied structures of knee joint. Furthermore, new interactions among these toxic elements were noted.